Modulação autonômica da frequência cardíaca e treino de força excêntrica no processo de envelhecimento - Takahashi, Anielle Cristhine de Medeiros (2010)
The aging process is marked by several physiological changes, and the reduction in muscle strength is very important one. In order to minimize this force decline there are recommendations for using resistance training for elderly persons. Some studies available in the literature state that the eccentric contraction would be more suitable for the elderly, since it generates less cardiovascular overload during the exercise. However, the chronic effect of the eccentric strength training (EST) on the heart rate (HR) autonomic modulation is unclear. So, the aim of the first study was to investigate whether the EST changes HR and heart rate variability (HRV) during submaximal isometric contractions (SIC). This study included 17 volunteers who form divided into two groups: training group (9 men, 62 ± 2 years) and control group (8 men, 64 ± 4 years). The results indicate that although this type of training improves eccentric strength, the EST does not have any effect sufficient to promote changes in the autonomic control of HR during isometric exercise. Another important factor to consider is the increase in incidence of cardiovascular disease that occurs with aging. Furthermore, there are modifications of autonomic control of HR related to ageing that are detected by the reduction in HRV and changes in the complexity of physiological dynamics. Based on these considerations the aim of the second study was to verify whether changes in HR modulation, caused by the aging process, can be detected by the Shannon entropy (SE), conditional entropy (CE) and symbolic analysis (SA). In this study were evaluated 21 elderly (63 ± 3 years) and 21 young (23 ± 2 years). Elderly present distributions of patterns in HRV that are similar to young subjects. However, the patterns are more repetitive, thus reducing the complexity. This decrease of complexity comes from the increased presence of stable patterns and a decreased presence of highly variable patterns. This difference indicates that apparently healthy older subjects have a marked unbalance in autonomic regulation. The results of the second study indicate that non-linear approaches might be helpful to better characterize the changes on the autonomic control of HR in the aging process.